Primary osteosarcoma of the thyroid gland – a case report - Zembala-Nożyńska, Ewa; Lange, Dariusz (Contemporary Oncology/Współczesna Onkologia, 2013)
A rare localization of primary osteosarcoma is presented. A woman aged 76 years was operated on for rapid growth of thyroid right lobe tumour. Histopathology showed anaplastic cancer with numerous foci of osseous metaplasia, negative with thyroglobulin, calcitonin, synaptophysin and chromogranin. A high proliferative activity of the tumour was observed (MIB-1 reaction) in the form of a positive reaction in approx. 40% of the tumour cell nuclei. The tumour stage was evaluated as pT4aNxMx according to the TNM scale. The reconsultation revealed negative staining with cytokeratin, and positive with vimentin, thereby confirming the mesenchymal origin of the tumour, with the final diagnosis being primary thyroid osteosarcoma. Taking into consideration the histopathological diagnosis, the extremely low radiation sensitivity of the tumour, the patient's age, the radical surgical treatment and persisting respiratory failure, radiotherapy was rejected in favour of further follow-up. The patient remains under oncological and endocrinological care.